An economic order quantity model for Pareto distribution deterioration with linear demand under linearly time-dependent shortages. (17th March 2022) - Sindhuja, S.; Arathi, P.
The inventory models for deteriorating items aim to reduce the total cost under normal market conditions. This paper focuses on the possible effects of minimising total cost by developing an economic order quantity (EOQ) model, where the deterioration is considered as Pareto distribution with linear demand. This model is applicable for vegetable vendors to make inventory decisions in the inventory system under the influence of optimal values. The linear demand and shortage of cost are also taken into consideration. To illustrate the proposed EOQ model, numerical examples and corresponding sensitivity analysis on the parameters A, c, d, pc, h, s, α and β are discussed and compared with the existing models. The result of the model developed in this paper is based on the deterioration leading to significant effects of the Pareto distribution deterioration variables α and β on the 'total cost'. The complex algebraic equations are solved using MATLAB R2013a. [Submitted: 11 January 2021; Accepted: 12 April 2021]